(untitled) (Revista Inclusiones, 2020)
The study describes the sequence of formation and use of paradigms as conceptual research models. Based on the presentation of their genesis and identification of common features, the importance of information support of both the real practice of society and its study is shown. In this regard, the role of using the information research paradigm is shown and several new elements are identified that reflect the need not only to identify emerging problems, but also the possibility of solving them. The multidimensionality, constructivism, optimization approach, multilevelness of the studied subjects, and the analysis of a larger number of influencing factors are interpreted in the text as elements of the modern research paradigm, which has a capacious content and is constantly enriched with new semantic elements.